2020
DOI: 10.1038/s41598-020-79125-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of 5-fluorodeoxyuridine and doxorubicin via gold nanoparticle equipped with affibody-DNA hybrid strands for targeted synergistic chemotherapy of HER2 overexpressing breast cancer

Abstract: Combination chemotherapy is still of great importance as part of the standard clinical care for patients with HER2 positive breast cancer. As an attractive component, gold nanoparticles (AuNPs) have been extensively studied as biosafety nanomaterials, but they are rarely explored as drug nanocarriers for targeted co-delivery of multiple chemotherapeutics. Herein, a novel affibody-DNA hybrid strands modified AuNPs were fabricated for co-loading nucleoside analogue (5-fluorodeoxyuridine, FUdR) and anthracycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
(49 reference statements)
0
16
0
1
Order By: Relevance
“…demonstrate that affibody molecule is an excellent target ligand that has the advantages of low molecular weight (7 kDa), stable structure and function, high selectivity and affinity [40][41][42]. In this regard, affibody as a targeting moiety will be employed to develop a variety of drug delivery systems for the treatment of HER2-positive tumors [43][44][45]. In this study, 5-fluorodeoxyuridine (FUdR, metabolite of 5-Fluorouracil) and curcumin (Cur) were chosen as a model hydrophobic drug and hydrophilic drug due to their good synergistic effect in cancer treatment [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrate that affibody molecule is an excellent target ligand that has the advantages of low molecular weight (7 kDa), stable structure and function, high selectivity and affinity [40][41][42]. In this regard, affibody as a targeting moiety will be employed to develop a variety of drug delivery systems for the treatment of HER2-positive tumors [43][44][45]. In this study, 5-fluorodeoxyuridine (FUdR, metabolite of 5-Fluorouracil) and curcumin (Cur) were chosen as a model hydrophobic drug and hydrophilic drug due to their good synergistic effect in cancer treatment [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on active targeting of drug-loaded AuNPs using cancer targeting ligands such as antibodies, peptides, and small molecules also have been reported [ 53 ]. Zhang et al developed 5-fluorodeoxyuridine (FUdR) and Dox co-delivery systems using HER2-specific affibody-functionalized AuNPs [ 54 ]. They conjugated FUdR containing DNA to HER2-specifc affibody and attached the affibody-DNA hybrid to AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Yeom et al engineered BAX mRNA-loaded AuNP–DNA conjugates and then injected them into xenograft tumors in mice, resulting in highly efficient mRNA delivery and biologically functional BAX protein (a proapoptotic factor) production, subsequently inhibiting tumor growth [ 159 ]. Moreover, Zhang et al demonstrated that DNA-attached AuNPs are more easily taken up by cells and are highly stable in serum-containing solutions [ 160 ].…”
Section: The Nonviral Nanodelivery Systems Of Mrna Vaccinesmentioning
confidence: 99%